-46=-2x-3x-6

Simple and best practice solution for -46=-2x-3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -46=-2x-3x-6 equation:


Simplifying
-46 = -2x + -3x + -6

Reorder the terms:
-46 = -6 + -2x + -3x

Combine like terms: -2x + -3x = -5x
-46 = -6 + -5x

Solving
-46 = -6 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-46 + 5x = -6 + -5x + 5x

Combine like terms: -5x + 5x = 0
-46 + 5x = -6 + 0
-46 + 5x = -6

Add '46' to each side of the equation.
-46 + 46 + 5x = -6 + 46

Combine like terms: -46 + 46 = 0
0 + 5x = -6 + 46
5x = -6 + 46

Combine like terms: -6 + 46 = 40
5x = 40

Divide each side by '5'.
x = 8

Simplifying
x = 8

See similar equations:

| 4+4x=16+4x | | -4+3x+6x=41 | | 6x-8y=-4 | | 75=0.2*x | | 2x^2-3x+18=0 | | 5+9i/1+i | | z/3-8=14 | | 56x-14/24x-6 | | x+2x+x=y | | 21/3+r=43/4 | | 4(3a+6)= | | 3(d-5)=15 | | 40+x=2x | | X+3=9+2 | | -5x-9=-14 | | 1/10r=41/2 | | 3x-5x=-10-20 | | 2-x=3x+6 | | (p^2-4p-21)/(p^2-2p-35) | | 2/7r=6 | | X+x=10-2 | | 4x=136+9x | | 9-10x=83-24x | | 31x+21x=21 | | 4x+3x=10+4 | | 10=4*T*20/100 | | -64x^2+104x= | | 4x+x+20=200 | | 4/3r=31/2 | | 28=4-3p | | -43-4=7-9x | | x+x+20=200 |

Equations solver categories